2015
DOI: 10.1080/13527266.2015.1061037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marketing activities, benefits, risks, confusion due to over-choice, price, quality and consumer trust on online tourism purchasing

Abstract: Pappas, Nikolaos (2015) Effect of marketing activities, benefits, risks, confusion due to over-choice, price, quality and consumer trust on online tourism purchasing. Journal of Marketing Communications. ISSN 1352-7266 Downloaded from: http://sure.sunderland.ac.uk/6489/ Usage guidelinesPlease refer to the usage guidelines at http://sure.sunderland.ac.uk/policies.html or alternatively contact sure@sunderland.ac.uk.The effect of marketing activities, benefits, risks, confusion due to over-choice, price, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 95 publications
(74 reference statements)
3
40
0
2
Order By: Relevance
“…More recently, with the rise of online shopping and service delivery, perceived risk became a key issue for online behaviour (Mou, Shin, & Cohen, 2017;Pappas, 2017b;Zhou, Dai, & Zhang, 2007). Some of these risks are related to personal data and financial transactions security, whereas others include the performance of the product and the fear of buying fake or smuggled products, and of wasting money and time unwisely (Chen, Yan, Fan, & Gordon, 2015;Hubert et al, 2017;Nepomuceno et al, 2014;Pappas, 2017a;Ponte et al, 2015). Despite the growth of the research on this topic, previous results are not consistent (Chang & Chen, 2008;Chang et al, 2005;Mou et al, 2017).…”
Section: Literature Review 1perceived Risk Trust and Online Purchasmentioning
confidence: 96%
See 3 more Smart Citations
“…More recently, with the rise of online shopping and service delivery, perceived risk became a key issue for online behaviour (Mou, Shin, & Cohen, 2017;Pappas, 2017b;Zhou, Dai, & Zhang, 2007). Some of these risks are related to personal data and financial transactions security, whereas others include the performance of the product and the fear of buying fake or smuggled products, and of wasting money and time unwisely (Chen, Yan, Fan, & Gordon, 2015;Hubert et al, 2017;Nepomuceno et al, 2014;Pappas, 2017a;Ponte et al, 2015). Despite the growth of the research on this topic, previous results are not consistent (Chang & Chen, 2008;Chang et al, 2005;Mou et al, 2017).…”
Section: Literature Review 1perceived Risk Trust and Online Purchasmentioning
confidence: 96%
“…However, findings are inconsistent concerning the relationship between perceived risk and trust (Hong, 2015). While some studies concluded that trust can be a strong predictor for reducing perceptions of risk (Agag & El-Masry, 2017;Büttner & Göritz, 2008), others found the opposite relationship (Pappas, 2017a;Ponte et al, 2015;Sharma et al, 2017). Others, still, propose a reciprocal relationship between the two constructs (Chang & Chen, 2008;Comegys et al, 2009).…”
Section: Literature Review 1perceived Risk Trust and Online Purchasmentioning
confidence: 99%
See 2 more Smart Citations
“…These behavioural changes led to the development of online booking channels, including OTAs. Although some studies argue that there are no significant differences between traditional and online commerce, many claim that there is a new stage in the purchasing process: the stage of trust-building (Lee, 2002;Pappas, 2017). There are several studies on this subject, focusing on the use of the internet in the process of planning a trip (Ferrer-Rosell, Coenders & Marine-Roig, 2017).…”
Section: Online Distribution Channels: Otasmentioning
confidence: 99%